2022
DOI: 10.1111/jam.15410
|View full text |Cite
|
Sign up to set email alerts
|

Identification of lead-resistant rhizobacteria of Carthamus tinctorius and their effects on lead absorption of Sunflower

Abstract: Aims: Using rhizobacteria as plant growth-promoting agents for improving heavymetal phytoremediation processes in contaminated soil has attracted a lot of attention mainly because of their eco-friendliness. The aim of this study was the evaluation of lead phytoremediation by Carthamus tinctorius improved with the isolated and molecularly identified lead-resistant rhizobacteria. Methods and Results: Rhizobacteria were isolated from C. tinctorius root and was identified using macroscopic and microscopic characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 27 publications
(30 reference statements)
0
2
0
Order By: Relevance
“…These bacteria with higher abundance (such as Acidobacteria and Bacteroidetes ) can improve the enrichment ability and growth ability of hyperaccumulators in a heavy metal environment. In addition, the bioavailability of metal elements in rhizosphere soil is significantly correlated to the relative abundance of the plant bacterial community (Hou et al, 2017; Shahraki et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…These bacteria with higher abundance (such as Acidobacteria and Bacteroidetes ) can improve the enrichment ability and growth ability of hyperaccumulators in a heavy metal environment. In addition, the bioavailability of metal elements in rhizosphere soil is significantly correlated to the relative abundance of the plant bacterial community (Hou et al, 2017; Shahraki et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Ramaiah and Vardanyan [ 37 ], in their study to evaluate the detoxification potential of cadmium and lead, investigated the bacteria, Alcaligenes faecalis , Bacillus pumilus , Pseudomonas aeruginosa , and Brevibacterium iodinium , which are highly resistant to mercury and can grow at 25 ppm or higher mercury concentrations, in a growth medium of 100 ppm and 72 ppm, respectively. They wereobserved to remove more than 70% of Cd and 98% of Pb within 96 h. Shahraki et al [ 38 ] found that Pseudomonas fluorescens and B. cereus strains had the greatest effect on lead assimilation at 2175 and 1862 ppm, respectively. Bilal et al [ 39 ] found that co- refinement of LHL10 and LHL06 promoted plant growth characteristics and photosynthetic activity, glutathione, catalase and superoxide dismutase activities, and decreased lipid peroxidation by increasing macronutrient uptake under high temperature and drought stress.…”
Section: Introductionmentioning
confidence: 99%